Abolition of the death penalty : SAHRDC's submission to the National Commission for the Review of the Working of the Constitution. - South Asia Human Rights Documentation Centre (New Delhi : South Asia Human Rights Documentation Centre, 2000)
With reference to India.
Keywords: Capital punishment -- India